Testate Amoebae and Nutrient Cycling with Particular Reference to Soils - Wilkinson, David M.; Mitchell, Edward (My University, 2010)
We asked the following question: Is the lack of attention given to testate amoebae, and other protists, in studies of nutrient cycling justified by their relative unimportance or are we ignoring key players in nutrient cycling and other ecological processes? We review various aspects of the ecology of testates relevant to their role in nutrient cycling. These include their food sources, their population sizes and production ecology, the rate of test breakdown ( and hence recycling of material from testates to other organisms) and non-feeding interactions with other organisms (e.g., mychorrhizae). Much of the relevant published literature dates from the late 1960s to the early 1980s, presumably due to the interest in production ecology and other aspects of ecosystem ecology at this time. There was a reduction in relevant research during the 1980s and 1990s, but there has recently been signs of renewed interest in this area. In addition to reviewing the past literature we suggest new speculations about the role of the evolution of grasses and the rise of the euglyphid testates-mediated by the silica cycle. Our main conclusion is that we currently do not know enough to answer our question about their potential importance! However, there are hints in these data which suggest that testates may be important and should be targeted by future research. Some of the main questions that should be targeted are outlined.